Kunstpflege in Bibliotheken - Kür oder Pflicht? Wege zur Sichtbarmachung forschungsrelevanter Druckgrafik an der Staats- und Universitätsbibliothek Hamburg - Kunze, Sophia; Posselt-Kuhli, Christina; Theise, Antje (Hamburg University Press, 2020)
Rarely is the collecting of prints in libraries looked at more closely, although this was still intensively cultivated in the 19th century, especially in Hamburg's active bourgeois culture. Once again, it becomes apparent that trade and artistic sensibility certainly went hand in hand in the Hanseatic city. Studying the copperplate engravings in the Hamburg State and University Library has brought to light a variety of traces that point to the provenances of the original owners and to the way the library dealt with them. They have been examined in detail and with dedicated research work by a group of art history students and presented in this book in a scientifically sound manner with new perspectives. In addition to the ramified history of the collection, the book also aims to draw attention to the works themselves, which are now digitally recorded and thus accessible. The publication combines both historical-critical library and collection history as well as an examination of modern instruments for making them available.